PENGEMBANGAN KEPEDULIAN SOSIAL WARGA NEGARA MELALUI KEBIJAKAN PEMERINTAH DAERAH MENGENAI ZAKAT, INFAK, DAN SHADAQAH - Kusnadi, Ade Engkus (Sosio Religi: Jurnal Kajian Pendidikan Umum, 2018)
This research is motivated by the potential zakat, infak, and shadaqah in Bandung regency untapped optimally. Meanwhile, the level of public awareness is relatively good Bandung regency is supported by the Regional Regulation Number 5 Year 2009 regarding Zakat, Infak, and Shadaqah (ZIS) and Regulation of Regent Number 1 Year 2006.  Departing from these conditions, this study aims to determine the development efforts through policy concern ZIS. With qualitative approach and case study design, this study collected data through library research, interviews and observations involving participants from BAZNAS Regency Bandung to explain the development of awareness of citizens through the policies of the ZIS. From these results it appears that the existing policy has not been able to develop optimally caring citizens. Recommendations are given is to maximize the efforts of all parties to realize the concerned citizens through policies ZIS.